Conceptual framework of Workplace Flexibility and Positive Working Environment - Jahagirdar, Renu; Bankar, Dr. Swati (The journal of contemporary issues in business and government, 2022)
Background - In today's companies, adaptable work arrangements are becoming more important. Due to the obvious advantages of flexibility, many businesses give adaptable working arrangements to all the people and the company. Increased worker productivity and corporate profitability are two of their most prominent benefits. Adaptable work schedules also aid in the attainment and maintenance of a good work-life balance. Employee well-being and stress levels are decreased when work-life balance is maintained. Workplace Environments, such as flexibility, are evolving and have an impact on employee health Conditions. Working from residence, taking time off are required, and modifying one's work pattern are all examples of work flexibility. The majority of Employees assert that having a great attitude in a Positive work environment improves the productivity of the Organisation and decreases the employee difficulties such as physical and mental stress, road traffic, work in non-flexible timings, and unbalancing to care of family members in between the work Schedule. The fundamental purpose of the research is to evaluate the concept of a better workplace environment in the business of any organization. A descriptive design has been chosen to describe the impact of current workplace flexibility on employee performance. The particular study has some limitations because the topic is controversial. Some employees are satisfied with the current work situation and others are complaining about it. On the other hand, for conducting the study, a proper survey procedure could not be accomplished. Contribution - A positive workplace can foster the growth of any organization and also reduce workplace stress. A flexible working environment can promote workplace health and safety. Leaders are the main contributor to take decisions for any company and also construct a proper framework for a flexible workplace.